Leitlinien reformatorischer Ekklesiologie. Das Beispiel Calvins - Beintker, Michael (Zeitschrift für Theologie und Kirche, 2017)
John Calvin was a second generation Reformer and as such represented an ecclesiology in which new evangelical insights were consolidated and further developed. His doctrine of the church is characterized by conceptual power and excellence, and is one which deeply influenced the Reformed churches by connecting theology with the principles of ecclesiastical order. Indeed, Calvin's concepts are still capable of greatly animating today's ecclesiology.